The effect of implementing plastic ball in Chinese excellent female table tennis players' technique and tactics performances - Lin, Y.; Liu, C.; Zhang, Y. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
According to the regulation launched by ITTF (International Table Tennis Federation), the official materials utilized in manufacturing table tennis balls have been changed from celluloid to plastic since 1st of July, 2016. That is to say, from then on, plastic ball has officially emerged on ITTF events. The main purpose of this study aimed to explore the effect of implementing plastic ball in Chinese excellent female table tennis players` technique and tactics performances (i.e. three-part skill performances) during the early transition period (from February 2013 to August 2015). This study had been done with the eyes on 32 games (177 rounds in total) participated by Xiaoxia Li, Ning Ding, Shiwen Liu and Lingyu Zhu, and with the method of video observation, mathematical statistics and comparative analysis. Based on the research, the developing tendency of plastic ball can be anticipated will be better and better. The research results can be concluded as follows. (1) After using plastic ball, there was less effect in serve-then-aggress part while was quite large effect in receive-then-aggress part and there was great effect in rally part. (2) Using plastic ball contributes to serve-then-aggress part that players were easier to attack rivals. (3) The athletes benefited from using plastic ball in receive-then-aggress part that they were more proactive even were capable to change situations from passive to active. (4) When using plastic ball, the rounds that athletes played in rally part were increased so that the competitions would be more eye-catching. According to the conclusion, it could be found that using plastic ball has exactly affected female players` technique and tactics performances (i.e. three-part skill performances). It brought positive effects on Xiaoxia Li, Shiwen Liu and Lingyu Zhu while brought negative effects on Ning Ding.